ANALYZING PEDAGOGICAL KNOWLEDGE OF HIGH SCHOOL BIOLOGY TEACHERS IN BANTEN BASED ON EDUCATIONAL BACKGROUNDS - Rahayu, Maya; Suyanto, S (Journal of Biology Education, 2019)
formulate the learning plan, method comprehension and approach, curriculum, learning motivation as well as learning evaluation instrument. This research was aimed to discover the skill difference of pedagogical knowledge of biology teachers compared to different educational backgrounds. The method of this research was a quantitative-descriptive through proportional random sampling technique for sample collection. The population of this research was the entire biology teachers in State High School of Lebak Banten. The collected samples were 18 biology teachers with different educational backgrounds. This research was performed in State High Schools spread among the area of Lebak-Banten. The analysis results of the data of pedagogical knowledge question items have indicated that the average teachers with biology education background has higher score (73.33) and 0.033<0.05 value has acquired based on t-test result. It means that there is a significant difference between teachers who have biology education background compared to teachers with non-education backgrounds